Limbic Encephalitis: Potential Impact of Adaptive Autoimmune Inflammation on Neuronal Circuits of the Amygdala - Melzer, Nico; Budde, Thomas; Stork, Oliver; Meuth, Sven G. (Frontiers in Neurology, 2015)
Limbic encephalitis is characterized by adaptive autoimmune inflammation of the gray matter structures of the limbic system. It has recently been identified as major cause of temporal lobe epilepsy accompanied by progressive declarative – mainly episodic – memory disturbance as well as a variety of rather poorly defined emotional and behavioral changes. While autoimmune inflammation of the hippocampus is likely to be responsible for declarative memory disturbance, consequences of autoimmune inflammation of the amygdala are largely unknown. The amygdala is central for the generation of adequate homoeostatic behavioral responses to emotionally significant external stimuli following processing in a variety of parallel neuronal circuits. Here, we hypothesize, that adaptive cellular and humoral autoimmunity may target and modulate distinct inhibitory or excitatory neuronal networks within the amygdala and thereby strongly impact processing of emotional stimuli and corresponding behavioral responses. This may explain some of the rather poorly understood neuropsychiatric symptoms in limbic encephalitis.